2018
DOI: 10.1155/2018/4540387
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Analysis, and Design of a Fuzzy Logic Controller for an AHU in the S.J. Carew Building at Memorial University

Abstract: Proper functioning of heating, ventilation, and air conditioning (HVAC) systems is important for efficient thermal management, as well as operational costs. Most of these systems use nonlinear time variances to handle disturbances, along with controllers that try to balance rise times and stability. The latest generation of fuzzy logic controllers (FLC) is algorithm-based and is used to control indoor temperatures, CO 2 concentrations in air handling units (AHUs), and fan speeds. These types of controllers wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Meanwhile, in the real system (as shown in Figure 2), a hot Journal of Energy 3 water valve collects relevant data for water heated by a heating coil. Although the building's system features a single valve for its hot water production, the IDA-ICE software divides the single valve into four distinct units, enabling each airhandling unit (AHU) to have an individual valve [22,23].…”
Section: Simulation Toolmentioning
confidence: 99%
“…Meanwhile, in the real system (as shown in Figure 2), a hot Journal of Energy 3 water valve collects relevant data for water heated by a heating coil. Although the building's system features a single valve for its hot water production, the IDA-ICE software divides the single valve into four distinct units, enabling each airhandling unit (AHU) to have an individual valve [22,23].…”
Section: Simulation Toolmentioning
confidence: 99%
“…CO2 levels )unit is parts per million, PPM) for controlling fresh air dampers. A detailed state space model used for controller design for AHU1 was presented in [29].…”
Section: Input Data Reportmentioning
confidence: 99%
“…To increase the output gain, the tuning of a PI controller can be used, as described the outputs of the first AHU1 in the following subsections [29]. Also, the table 4 illustrate all the details of MFs (Close-Fast, Close, No-Change, Open and Open-Fast) and the related operation percentages of hot water valve's, fan speed and fresh air dampers of whole system.…”
Section: Sflc Input Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the FLC also is developed and employed to decrease power consumption and cost of both illumination and HVAC systems, resulting in a significant reduction in the energy consumption, monetary cost, and peak to average ratio (PAR). Abdo-Allah et al [20] concluded that the function of HVAC systems are significant for effective thermal management and operational costs. Therefore, the FLC is used to control indoor temperatures, CO2 concentrations in air handling units (AHUS), fan speeds and power consumption.…”
Section: Introductionmentioning
confidence: 99%